Correction: Martin et al. The FeetMe® Insoles System: Repeatability, Standard Error of Measure, and Responsiveness. Sensors 2024, 24, 6043 - Nathan Martin; Fabien Leboeuf; Didier Pradon (Sensors)
In the original publication [...]